Karakteristik dan problematika siswa sekolah dasar - Atika Dwi Evitasari (Universitas Sebelas Maret, 2024)
Abstract. Learning in elementary school is different from the learning process at other levels of education. Learning in elementary schools considers aspects of elementary school student development which consist of aspects of physical development, emotional development, social development and intellectual development. The amount of learning that is not in accordance with learning characteristics will have an impact on the quality of learning and give rise to problems within the scope of elementary school students. The purpose of this writing is to provide information regarding the characteristics and problems of elementary school students. The writing methodology uses the literature study method. Based on the studies that have been presented, there are types of development of elementary school students that teachers need to know, namely physical, emotional, social and intellectual development. Meanwhile, problems with elementary school students in Indonesia include disruption of children's social-emotional development, weak character education for children, and violence against children.Keywords: characteristics, problems, elementary school students